Teaching-Service Integration in Health Training:: Potentialities and Operationalization Process of Integrated Curriculum - Yamashita, karen; Quaglio Chirelli, Mara; Franco da Rocha Tonhom, Silvia; Fernandes Biffe Peres, Cássia Regina; Abdel Massih Pio, Danielle (Cadernos de Educação Tecnologia e Sociedade, 2023)
The creation of the Unified Health System, the displacement of the referential from qualification to competence, the changes in epidemiological and demographic profile with their unfolding in the care needs encourage debates and discussions about curricular change to achieve the training of health professionals proposed in National Curricular Guidelines. One of the possibilities has been to organize the training based on an integrated curriculum and active teaching-learning methodologies. The teaching-service partnership has proven to be an important strategy for the implementation of this curricular organization. Thus, it is important to understand how the negotiation/agreement between teaching and service occurs and what is known about the agreement and contributions in the training of nurses and physicians. The present study aimed to analyze how the pacts occur and what contributions they make to the training of nurses and doctors, considering the teaching-service partnership. Qualitative research carried out with managers from the academy and service, preceptors and teachers. Data were collected through semi-structured interviews with eleven managers, eight teachers and nine preceptors from the service. Content analysis, thematic modality was used in processing the data. It was identified that the understanding about negotiation/partnership process was stronger in the past with the involvement of academy’s and service’s managers and there is a lack of knowledge of service’s preceptors about the subject. Teaching-Health Public Action Organizational Contract (COAPES) is a strategy for strengthening the partnership, but it has not helped in organizing the operationalization. As potentialities, the early insertion of students in practice scenarios, co-responsibility of the preceptor with the students' training, resolution of community needs, and training of service’s preceptors. Therefore, teaching-service partnership is essential in the operationalization of the training with integrated curricular organization and in the dialogical approach of competence, requiring from the partners willingness to build new practices from the pacts, being permanent education the space for dialogue and reconstruction from the critical reflection on the daily work.